Universal Health Care 101 : Lessons for the Eastern Caribbean and Beyond - Tsounta, Evridiki (Washington, D.C. : International Monetary Fund, 2009)
Despite the increasing interest in universal health care, little is known about the optimal way to finance, design, and implement it. This paper attempts to fill this gap by providing some general policy recommendations on this important issue. While most of the paper addresses the Eastern Caribbean Currency Union (ECCU) countries, its policy implications are applicable to any country. The paper finds that the best financing option is country-specific depending on a country's economic, cultural, institutional, demographic and epidemiological characteristics, as well as political economy considerations. However, taxation should be the primary financing source. It also concludes that an appropriate and realistic benefit package would need to be designed to ensure the system's financial viability. Regarding the optimal way to implement universal health care, certain preconditions are needed, including sound public administration, a small informal economy, and a transparent health financing system that builds social consensus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet